Pessimismo e sabedoria de vida na filosofia de Arthur Schopenhauer: uma proposta didática para o ensino médio - Moraes, Newton Carlos Forte (2024)
The present dissertation aims to present a didactic proposal for High School that aims to contemplate Arthur Schopenhauer's philosophy, demonstrating its potential and its reach in the context of basic education. Initially, we will analyze and reconstruct his main theoretical assumptions, more precisely, with regard to his conception of the world as will and as representation; his philosophical pessimism as a judgment of value or disvalue of existence; the notions from the ethical-metaphysical point of view and the ways of denying the will; the feeling of compassion as the foundation of morality; the notions of human character and perfectibility and ethical considerations of a pragmatic nature taken as life wisdom that indicates ways to understand and endure the adverse events of life and the world. In a second moment, we will present an educational pedagogical product that consists of the proposal of a didactic sequence aimed at high school, which aims to contemplate the aforementioned philosophical elements described above in a teaching practice that attests to the pertinence and relevance of these elements in facing themes and events that emerge from contemporary problems. This product aims to promote the development of the ability to reflect, contextualize and problematize current themes in comparison with the issues highlighted and faced by the philosopher of Will in the context of his work. We will seek to follow the path of reflections followed by the philosopher Arthur Schopenhauer in his philosophical system, replacing the primordial questions raised by him and reflecting on their causes and foundations, repositioning the problems to the context currently experienced in order to articulate communication between the acquired knowledge, and the context and experiences of students themselves.